2019
DOI: 10.2151/jmsj.2019-025
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Relationship between Upper Tropospheric Cold Lows and Tropical Cyclone Genesis over the Western North Pacific

Abstract: This study examined the statistical characteristics of tropical cyclones (TCs) for which the cyclogenesis (TCG) process was modulated by upper tropospheric cold lows (UCLs) over the western North Pacific during the 38 years from 1979 to 2016. Among the 965 TCs, 90 TCs (9 %, 2.4 per year) were defined as having TCG influenced by UCLs in the northwest quadrant of the TC region (UL-TCs). Most UL-TCs occurred in the summer, with large variability in the annual occurrence rate of UL-TCs during June to October, rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The GPI estimates the favourability of TC formation using large‐scale environmental parameters (e.g., low‐level vorticity, mid‐level relative humidity, the deep‐layer vertical shear of the horizontal wind and the maximum potential intensity, which reflects the vertical thermodynamic structure of the atmosphere). However, answering the question “why is the GPI unable to represent the TC genesis density anomaly in some months?” is beyond the scope of the present study but it is noteworthy that TCs form from tropical disturbances (e.g., mixed Rossby‐gravity waves or tropical depressions; Takayabu & Nitta, 1993) as well as extratropical systems (e.g., upper tropospheric cold lows; Fudeyasu & Yoshida, 2019). Indeed, Fudeyasu and Yoshida (2019) showed that the number of TC geneses from the upper tropospheric cold lows is the highest in August.…”
Section: Summary and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The GPI estimates the favourability of TC formation using large‐scale environmental parameters (e.g., low‐level vorticity, mid‐level relative humidity, the deep‐layer vertical shear of the horizontal wind and the maximum potential intensity, which reflects the vertical thermodynamic structure of the atmosphere). However, answering the question “why is the GPI unable to represent the TC genesis density anomaly in some months?” is beyond the scope of the present study but it is noteworthy that TCs form from tropical disturbances (e.g., mixed Rossby‐gravity waves or tropical depressions; Takayabu & Nitta, 1993) as well as extratropical systems (e.g., upper tropospheric cold lows; Fudeyasu & Yoshida, 2019). Indeed, Fudeyasu and Yoshida (2019) showed that the number of TC geneses from the upper tropospheric cold lows is the highest in August.…”
Section: Summary and Discussionmentioning
confidence: 92%
“…However, answering the question “why is the GPI unable to represent the TC genesis density anomaly in some months?” is beyond the scope of the present study but it is noteworthy that TCs form from tropical disturbances (e.g., mixed Rossby‐gravity waves or tropical depressions; Takayabu & Nitta, 1993) as well as extratropical systems (e.g., upper tropospheric cold lows; Fudeyasu & Yoshida, 2019). Indeed, Fudeyasu and Yoshida (2019) showed that the number of TC geneses from the upper tropospheric cold lows is the highest in August. Yoshida and Fudeyasu (2020) found that the frequency of the easterly wave flow pattern, which often transforms into tropical depressions, is the highest in October.…”
Section: Summary and Discussionmentioning
confidence: 92%
“…When a contributing factor could not be detected by the TGS algorithm, the flow pattern was categorized as unclassified flow (UCF). Details of the objective TGS algorithm are provided in previous studies [15,17,24].…”
Section: Methodsmentioning
confidence: 99%
“…They reported that the monsoon SL, monsoon CR, and EW patterns were the most frequent flow patterns over the WNP. The environment of the flow pattern also has an influence on the characteristics (e.g., strength and track) of the tropical cyclones after the TCG (Fudeyasu and Yoshida 2018). Yoshida and Ishikawa (2013) developed a semiobjective analysis method to categorize the five flow patterns for a longterm analysis, with a stable reliable criterion.…”
Section: Introductionmentioning
confidence: 99%